2022
DOI: 10.1021/acsomega.2c06633
|View full text |Cite
|
Sign up to set email alerts
|

Facile Surface Modification of MgMn2O4 Positive-Electrode Material for Improving Cycle Performance of Magnesium Rechargeable Batteries

Abstract: MgMn 2 O 4 with a tetragonal spinel structure shows promise as a positiveelectrode material in magnesium rechargeable batteries (MRBs), which have drawn considerable attention as post lithium-ion batteries. However, the material currently suffers from poor cycle performance. In this study, we attempt to improve the cycle performance of MgMn 2 O 4 via the Zr modification of its particle surface. X-ray photoelectron spectroscopy and energy-dispersive X-ray spectroscopy demonstrate that the surface modification i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Rietveld analysis showed that all of the Bragg peaks in the XRD pattern were attributed to the tetragonal spinel phase with a space group of I 4 1 / amd with lattice constants of a = 5.718(9) and c = 9.068(15) (Table S1). This structure is similar to the structure of ZnMn 2 O 4 and MgMn 2 O 4 ,,, reported in previous reports. The Zn:Mn ratio was 0.50, which was confirmed by ICP-OES measurements.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Rietveld analysis showed that all of the Bragg peaks in the XRD pattern were attributed to the tetragonal spinel phase with a space group of I 4 1 / amd with lattice constants of a = 5.718(9) and c = 9.068(15) (Table S1). This structure is similar to the structure of ZnMn 2 O 4 and MgMn 2 O 4 ,,, reported in previous reports. The Zn:Mn ratio was 0.50, which was confirmed by ICP-OES measurements.…”
Section: Resultssupporting
confidence: 91%
“…Among the 3d transition metal oxides, spinel oxides are the most promising because of their relatively high potential and capacity. In spinel oxides, it has been reported that Mg 2+ insertion/extraction reactions using Me 3+ /Me 4+ redox (Me: the transition metal in spinel oxide) and Me 2+ /Me 3+ redox are possible . However, electrolyte decomposition occurs due to the relatively high potential of Me 3+ /Me 4+ redox; , the use of Me 2+ /Me 3+ redox has attracted much attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation